Observation of Plasmoelectric Effect in Plasmonic Zirconium Nitride - Satoshi Ishii; Min‐Wen Yu; Kuo‐Ping Chen; Tadaaki Nagao (Advanced Materials Interfaces, 2023)
Abstract A plasmonic nanostructure forming a metal‐semiconductor interface generates electric potential by optical illumination. Grounded plasmonic nanostructures can also generate electric potentials based on the recently demonstrated plasmoelectric effect that allows all metallic photoelectric devices to be fabricated and is capable of generating negative and positive potentials at off‐resonance by merely tuning the illumination wavelength. However, to date, the plasmoelectric effect has been observed only with gold and silver. In this study, the generation of plasmoelectric effect by zirconium nitride (ZrN) is experimentally demonstrated, which is a nonmetallic plasmonic material. The Kelvin probe force microscope measurements demonstrate that ZrN nanodisk arrays fabricated through e‐beam lithography and dry etching exhibit characteristic potential sign changes of the plasmoelectric potential. The features of the wavelength‐dependent potential shifts in the experiments agree with the numerical calculations. It is anticipated that the plasmoelectric effect can be observed in other non‐metallic plasmonic materials and these studies may lead to robust photoelectric devices working at off‐resonances.